1985
DOI: 10.1038/jcbfm.1985.33
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acidosis and Recovery of Mitochondrial Function following Forebrain Ischemia in the Rat

Abstract: Summary:The effect of different degrees of lactic aci dosis on the recovery of brain mitochondrial function, measured as respiratory activity in isolated mitochondria or cortical concentrations of labile phosphates and car bohydrate substrates, was studied during 30 min of recir culation following 15 min of near-complete forebrain isch emia in rats. During ischemia, there was a marked de crease in mitochondrial State 3 respiration in vitro and a depletion of energy stores (i,e" phosphocreatine, ATP, glucose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
2
2

Year Published

1988
1988
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 34 publications
8
52
2
2
Order By: Relevance
“…Since calcium does not readily pass the blood brain barrier, it is hardly justified to discuss the ini tial shift of calcium from extra-to intracellular fluids in terms of "calcium overload. " This conclu sion is corroborated by results showing that the total tissue calcium content does not rise in the minutes and hours following transient ischemia of a duration that will, at a later stage, cause dense neu ronal necrosis (Dienel, 1984;Hillered et al, 1985;Deshpande et al , 1987).…”
Section: Discussionsupporting
confidence: 68%
“…Since calcium does not readily pass the blood brain barrier, it is hardly justified to discuss the ini tial shift of calcium from extra-to intracellular fluids in terms of "calcium overload. " This conclu sion is corroborated by results showing that the total tissue calcium content does not rise in the minutes and hours following transient ischemia of a duration that will, at a later stage, cause dense neu ronal necrosis (Dienel, 1984;Hillered et al, 1985;Deshpande et al , 1987).…”
Section: Discussionsupporting
confidence: 68%
“…Recovery of acid-base and ion homeostasis was observed in both groups of animals, although the extracellular pH decreased by 1 unit near the end of ischemia. Isolated mitochon dria resumed respiratory oxidation after 15 min of complete ischemia when incubated in 10 or 20 mmollL lactate (Hillered et al, 1985). In view of these results, Hillered et al (1985) proposed that acidosis is detrimental to the brain only if the isch emia has lasted for more than 15 min.…”
Section: Discussionmentioning
confidence: 97%
“…This result supports conclusions drawn from earlier studies that postischemic recovery of metab olism is not determined entirely by the duration of ischemia. Tissue acidosis is among those factors that influ ence postischemic recovery (Siesjo, 1985). In 1976, Myers and Yamaguchi reported that hyperglycemic animals suffer more severe ischemic brain damage than those with low blood glucose levels; the degree and extent of tissue damage was correlated with the content of lactic acid (Myers, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…With this model, hyperglycemia results in such a severe insult that survival is no longer possible, mainly because intractable seizures develop. 6,7 However, the ischemia does not compromise reflow since the bioenergetic state recovers upon reperfusion 16 and capillary patency remains intact. 17 It is thus possible to use the first hour of reperfusion to study events that prime the tissue for seizures and secondary bioenergetic failure.…”
Section: Discussionmentioning
confidence: 99%